The 2009 H1N1 Influenza Vaccination Campaign: Summary of a Workshop Series - Altevogt, Bruce M; Nadig, Lori; Stroud, Clare (National Academies Press, 2010)
The 2009 H1N1 vaccination campaign was one of the largest public health campaigns in U.S. history, vaccinating one-quarter of the population in the first three months. The Institute of Medicine held three workshops in Raleigh, NC; Austin, TX; and Seattle, WA to learn from participants' experiences during the campaign and improve future emergency vaccination programs.